AN INTERACTION-FOCUSED ANALYSIS OF THE YEDI IKLIM TÜRKÇE TEXTBOOK FOR TEACHING TURKISH TO FOREIGNERS (PALIMPSEST / ПАЛИМПСЕСТ, 2026)
This study aims to examine the activities in the Yedi İklim Türkçe B1 coursebook, which is widely used in teaching Turkish as a foreign language, in terms of interaction dimensions. The study employs a qualitative research design, utilizing the document review method. According to the examination, it was determined that the book contained a total of 235 activities. The activities were evaluated with an original analysis form that was created based on Littlejohn’s material analysis framework and included interaction features. The activities were analysed according to various criteria such as cognitive processes expected from the student, task type, communicative focus, interaction order, and content types used. The findings obtained within the scope of the examination show that the majority of the activities in the book are based on individual work, focus on the production of written output, and encourage limited use of language related to real life and based on meaning. In addition, it was determined that the productive activities that will enable students to think creatively, express their knowledge, and establish social interaction are limited. These findings reveal that the potential of the materials used in teaching Turkish as a foreign language to create interactive learning environments should be developed. The study offers concrete suggestions for material developers, instructors, and program designers, and aims to contribute to contemporary language teaching approaches that prioritize interaction.
Keywords: Teaching Turkish to foreigners; Turkish; coursebook; activity; interaction; review.